Dr. Kathleen Drew‐Baker, "Mother of the Sea", a Manchester scientist celebrated each year for half a century in Japan. (14th August 2013) - Harris, Constance; Matsuda, Kazuhiko; Sattelle, David B.
<x xml:space="preserve">Abstract</x> 2013 marks the 50th annual Drew festival in Uto City, Japan, celebrating the work of University of Manchester botanist, Dr. Kathleen Drew‐Baker. Her insight into the reproductive biology of algae was the key to efficient farming of the seaweed "nori" which is a familiar component of Japanese food. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>